The Significance of Serum Albumin Level as an Indicator for Severity of Hypertensive Disorders in Pregnancy in Samawa City (Medico Legal Update, 2021)
Background: This study is concerned with determining the severity of preeclampsia according to thevalue of serum albumin .Materials and Method : 100 women were divided into 4 groups according totheir blood pressure [control (n=22), gestational hypertension (n=25), mild preeclampsia (n=29), severepreeclampsia (n=24)].Concerning about comparison of serum albumin level for each woman . Also thefollowing informations were taken in consideration: age, gestational age, parity, systolic blood pressure anddiastolic blood pressure .Results : comparing serum albumin level between the groups shows a significantdifference (p?0.05). Analysis of data shows a significant difference in age between control and severepreeclampsia (p=0.04) . The difference in gestational age was significant between control and other groups(p?0.05) and a statistically significant difference in systolic and diastolic blood pressure between the groups(p?0.05). Conclusion: This study showed that serum albumin level is lower in mild and severe preeclampsiain comparison with normal and hypertensive cases.